Richard Jefferies After London ; or Wild England - Jefferies, Richard, 1848-1887 (Edinburgh critical editions of nineteenth-century texts., 2017)
A scholarly edition of a significant and exciting late Victorian science fiction novel. Richard Jefferies' After London is uncanny and intriguing, an adventure story, quest romance, dystopia, and Darwinian novel rolled into one, but also a pioneering work of Victorian science fiction. Imagining a mysterious natural catastrophe that plunges its people into a barbaric future, Jefferies remarkable novel drowns and destroys London and depicts a challenging ÃǾ²Ơ℗Wild England' dominated by nature and filled with evolved animals and devolved humans. Of its time but also distinctively modern, After London can, in its uneasy expression of Victorian and post-Victorian anxieties about industrial development, urbanisation, natural resources, and climate, be regarded as one of the first novels of the Anthropocene. This new critical edition provides one of the earliest examples of a global catastrophe novel that is part of a flowering of nineteenth-century science fiction. It situates After London in a tradition of mid-late Victorian texts that respond to the evolutionary theories of Charles Darwin and Alfred Russel Wallace and responds to a host of other key social, political, and cultural issues of the period. Key Features. Opens up readings that situate the text in relation to a range of literary, cultural and biographical contexts including Jefferies' life, ideas, and works Includes a chronology of Jefferies' life, a list of his key works, a detailed scholarly introduction, and appendices including the text of 'The Great Snow', a catastrophe short story set in London; and 'Alone in London'; both of which reveal his attitude to London, urban life and the future of humanity Richard Jefferies' After London is uncanny and intriguing, an adventure story, quest romance, dystopia, and Darwinian novel rolled into one, but also a pioneering work of Victorian science fiction. Imagining a mysterious natural catastrophe that plunges its people into a barbaric future, Jefferies' remarkable novel drowns and destroys London and depicts a challenging 'Wild England' dominated by nature and filled with evolved animals and devolved humans. Of its time but also distinctively modern, After London can, in its uneasy expression of Victorian and post-Victorian anxieties about industrial development, urbanisation, natural resources, and climate, be regarded as one of the first novels of the Anthropocene. This new critical edition provides one of the earliest examples of a global catastrophe novel that is part of a flowering of nineteenth-century science fiction. It situates After London in a tradition of mid-late Victorian texts that respond to the evolutionary theories of Charles Darwin and Alfred Russel Wallace and responds to a host of other key social, political, and cultural issues of the period.